PENGARUH KADAR RESIQUIMOD (R848) TERHADAP PERSENTASE SPERMATOZOA X DAN Y PADA SEMEN KAMBING PERANAKAN ETAWAH - NURHAYATI, SITI ZYA; Solihati, Nurcholidah; Setiawan, Rangga (Jurnal Produksi Ternak Terapan, 2025)
The swim up method is a method of selecting X and Y spermatozoa. This study aims to determine how resiquimod (R848) levels affect the percentage of X spermatozoa and Y spermatozoa in the semen of Etawah crossbreed goats (PE) resulting from sexing using the swim up method. This research was carried out from 1 - 30 January 2024 with the research object being male PE goats with a lifespan of 4 years. The research results were analyzed using variance, followed by Duncan's multiple range test to determine differences between treatments. In this study, four treatments were given, namely  (without R848),  (R484 0.3 μM),   (R484 0.6 μM), and  (R848 0.9 μM). Each treatment was repeated six times. The results of this study showed that the use of resiquimod (R848) did not have a significant difference in the percentage of X and Y spermatozoa. It can be concluded that it had no effect on the percentage of PE goat spermatozoa in the lower and upper layers.Keywords: Resiquimod (R848), Percentage of Spermatozoa, Swim up method, Goat PE